Nutritive value of forages as affected by soil and climatic differences - Richardson, D.; Banbury, Evans E.; Elliott, H.; Erhart, A.B.; Williams, G.; Russ, Oliver G.; Smith, E.F.; Harbers, L.H.; Adepoju, A.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
This is a progress report on the third test to determine whether there is a difference in the performance of beef steers due to location, soil, climate, rainfall and/or feed produced in farm areas of Kansas: Colby, Garden City, Manhattan, and Mound Valley. Forty-eight Hereford steer calves averaging 475 pounds and from the same herd as steers used in the second test were divided into four groups of 12 animals. One lots was assigned to each of the four locations. The test is being conducted in the same manner as the two previous tests except that concrete has replaced soil floors under the sheds.
Keywords: Beef; Forages; Soil; Climate; Performance